Pengaruh Pengalaman Pelanggan dan Kualitas Pelayanan terhadap Loyalitas Pelanggan dengan Citra Merek sebagai Pemediasi pada Pelanggan di Toko MM.Rabil - Bukhari, Ridhella; Putri, Della Asmaria (TSAQOFAH, 2026)
Customer loyalty is an important indicator of retail business sustainability, which is influenced by various factors, including customer experience, service quality, and brand image. This study aims to analyze the effect of customer experience and service quality on customer loyalty, with brand image as a mediating variable among customers of MM. Rabil Store. The research data were obtained through questionnaires distributed to 72 respondents and were then analyzed using the partial test (t-test). The results showed that brand image did not have a significant effect on customer loyalty. In contrast, service quality had a significant effect on brand image, but did not have a significant direct effect on customer loyalty. Customer experience was proven to have a significant effect on brand image and customer loyalty. In addition, brand image was not able to mediate the effect of either service quality or customer experience on customer loyalty. These findings indicate that customer loyalty at MM. Rabil Store is more directly influenced by customer experience, while service quality contributes more to the formation of brand image. Thus, this study emphasizes the importance of strengthening customer experience as the main strategy for increasing customer loyalty.